Anionic amide polymer and application thereof in saline-alkali soil improvement
By preparing β-cyclodextrin-2-acrylamide-2-methylpropanesulfonic acid-acrylamide copolymer, the problem that existing anionic polyacrylamide cannot effectively improve soil physical properties is solved, and soil water stability is achieved The increase in the number of particles, the decrease in soil bulk weight, and the improvement of soil permeability and porosity will maintain a good soil structure.
Patent Information
- Application Number
- CN202411435141.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing molecular weight and ionicity of anionic polyacrylamide cannot better improve soil physical properties, increase the number of soil water stability particles, reduce soil bulk weight, improve permeability and porosity, and maintain a good soil structure.
By selecting suitable raw materials and process conditions, a β-cyclodextrin-2-acrylamide-2-methylpropanesulfonic acid-acrylamide copolymer was prepared, and its molecular weight and ionicity were controlled to improve it in saline-alkali land. It has better water absorption and retention effect.
This copolymer can effectively improve soil physical properties, increase the number of soil water stability particles, reduce soil bulk weight, improve permeability and porosity, increase soil moisture content, and maintain a good soil structure.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soil improvement, and particularly relates to an anionic amide polymer and application thereof in saline-alkali land improvement. Background Art
[0002] With the continuous development of society, soil resources are becoming increasingly scarce. Furthermore, inappropriate use, such as excessive fertilizer application, excessive pesticide spraying, and overgrazing, has led to severe soil degradation. This degradation manifests itself in soil compaction and hardening, erosion, salinization, acidification, element imbalances, chemical contamination, loss of organic matter, and the degradation of flora and fauna. The consequences of soil degradation include reduced productivity, lowered crop quality, and even the accumulation of toxic elements. Therefore, maintaining soil quality, improving soil acidity and alkalinity, detoxifying soil, and reducing the spread of soil-borne diseases have become a major concern.
[0003] The application of soil conditioners is one of the important measures to repair degraded soil. Soil conditioners can effectively improve the physical and chemical properties of the soil and the soil nutrient status, and have a positive impact on soil microorganisms, thereby increasing the productivity of degraded soil. Soil properties include soil quality, soil moisture content, soil temperature, soil enzyme activity, soil microbial population, soil aeration conditions, soil solution concentration, and soil hydrogen ion concentration. Different types of soil conditioners have different mechanisms of action on the soil, but they all effectively improve the physical structure of the soil, reduce soil bulk density, increase soil moisture content, change soil chemical properties, increase soil microbial activity, enhance enzyme activity, increase soil trace element content, and adjust some or all of the soil water, fertilizer, air, and heat conditions to ultimately achieve the goal of improving soil fertility.
[0004] Polyacrylamide has a unique macromolecular structure that can achieve a sedimentation effect through adsorption bridging and charge neutralization. It has good adhesion to many microclusters and soluble substances in wastewater, making it a widely used flocculant in the water treatment industry, with broad application prospects and industrial application value. Polyacrylamide is a water-soluble chain polymer and is currently the most commonly used surfactant. The acrylamide in the molecular chain contains double bonds and amide groups with active properties, and various products can be obtained through various cross-linking and grafting copolymerization. For example, through a series of reactions, different types of cationic, anionic, and nonionic functional groups are added to synthesize amphoteric polyacrylamide, anionic polyacrylamide, and cationic polyacrylamide.
[0005] Although anionic polyacrylamide carries the same negative charge as the soil surface, it can combine with the soil through the action of cationic bridges. 2+ ) can combine with the surface of soil particles and the negative phase of anionic polyacrylamide to form a cationic bridge, namely PAM-Ca 2+- Soil particles. The degree of polyacrylamide absorption by soil particles depends on the properties of the polyacrylamide and the soil. Generally, the main influencing factors are the molecular weight and ionicity of the polyacrylamide, as well as the cation content in the soil. Polymers with high molecular weights and chain lengths are more effective in bridging fine soil particles and forming a protective network on the surface of aggregates, thus achieving better soil and water conservation results.
[0006] For example, Chinese patent CN106922245A discloses a soil improvement method in which anionic polyacrylamide is added to the soil conditioner used, which makes the invention effective in preventing soil erosion, greatly reduces the loss rate of dissolved fertilizer elements, and can increase the soil organic matter content. At the same time, it can adsorb both anions and cations.
[0007] For example, Chinese patent CN102487618A discloses a method for improving the soil structure of coastal dredger fill, comprising the following steps: adding water to polyacrylamide to adjust the concentration of polyacrylamide solution to 0.5-2.0 g / L, irrigating at a rate of 100-350 L / m 2 The polyacrylamide is an anionic polyacrylamide with a molecular weight of 8-12 million. This invention, by regulating the moisture content of the topsoil and the concentration of the polyacrylamide solution, gradually improves the clay structure of the dredger fill soil, establishes a stable aggregate soil structure, and significantly improves the permeability and water conductivity of the dredger fill soil, establishing a good channel for the migration of water, fertilizer, and salt in the dredger fill soil.
[0008] However, the molecular weight and ionicity of existing anionic polyacrylamide cannot better meet the needs. Therefore, it is necessary to develop an anionic polyacrylamide with moderate molecular weight and ionicity that can effectively improve the physical properties of the soil, increase the number of water-stable aggregates in the soil, reduce soil bulk density, increase permeability and porosity, increase soil moisture content, and maintain a good soil structure. Summary of the Invention
[0009] Based on the deficiencies in the prior art, the present invention aims to provide an anionic amide polymer, which is an anionic polyacrylamide. During the implementation process, by selecting anionic monomers, the molecular weight and ionicity of the obtained anionic polyacrylamide are moderate. When applied to saline-alkali land improvement, it can effectively improve the physical properties of the soil, increase the number of water-stable aggregates in the soil, reduce soil bulk density, increase permeability and porosity, increase soil moisture content, and maintain a good soil structure.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] An anionic amide polymer, wherein the anionic amide polymer is a β-cyclodextrin-2-acrylamide-2-methylpropanesulfonic acid-acrylamide copolymer, is prepared by the following method:
[0012] (1) adding sodium hydroxide solution to β-cyclodextrin until it is completely dissolved to obtain a β-cyclodextrin alkaline solution;
[0013] (2) adding the cyclohexane solution to the β-cyclodextrin alkaline solution, stirring rapidly until dispersed, then adding the initiator, crosslinking agent and emulsifier, and stirring until a stable emulsion is formed;
[0014] (3) adding acrylamide to water, stirring until completely dissolved, and then adding 2-acrylamido-2-methylpropanesulfonic acid to obtain a mixed solution;
[0015] (4) The emulsion obtained in step (2) is heated under reflux under nitrogen protection. When the temperature reaches 40° C., the mixed solution of step (3) is added dropwise to the emulsion, and the temperature is gradually raised to 60° C. After the reaction is completed, the emulsion is broken with anhydrous ethanol, washed, and dried to obtain the β-cyclodextrin-2-acrylamide-2-methylpropanesulfonic acid-acrylamide copolymer.
[0016] The concentration of sodium hydroxide in step (1) is 0.2-0.35 g / mL; preferably 0.25 g / mL.
[0017] The initiator in the above step (2) is coupled diisobutyronitrile;
[0018] The cross-linking agent in step (2) is N,N-2-methylbisacrylamide;
[0019] The emulsifier described in the above step (2) is Tween-80.
[0020] The volume ratio of the cyclohexane solution to the β-cyclodextrin alkaline solution in step (2) is 4-6:1, preferably 5.5:1.
[0021] The mass ratio of β-cyclodextrin, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide is 0.5-2:1-1.5:5-7;
[0022] Preferably, the mass ratio of β-cyclodextrin, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide is 0.8:1.2:6.5.
[0023] The amount of the initiator added is 0.2-0.4% of the total weight of the monomers, preferably 0.3%.
[0024] The amount of the cross-linking agent added is 0.03-0.06% of the total weight of the monomers, preferably 0.04%.
[0025] The amount of the emulsifier added is 5-8% of the total weight of the monomers, preferably 6%.
[0026] The mass volume ratio of acrylamide and water in step (3) is 0.15-0.20 g / mL, preferably 0.16 g / mL.
[0027] The speed of the dropwise addition in step (4) is 1-2 drops per second.
[0028] The heating rate in step (4) is 1°C per 2-3 minutes.
[0029] The reaction time in step (4) is 3-4 hours, preferably 4 hours.
[0030] The washing solvent in step (4) is anhydrous ethanol; the drying temperature is 40-50° C., and the drying time is 20-30 hours.
[0031] The present invention also provides the use of the above-mentioned β-cyclodextrin-2-acrylamide-2-methylpropanesulfonic acid-acrylamide copolymer in the preparation of a soil conditioner.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The present invention uses β-cyclodextrin, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide as raw materials to prepare a β-cyclodextrin-2-acrylamido-2-methylpropanesulfonic acid-acrylamide copolymer through inverse emulsion polymerization. The copolymer has good water absorption and water retention effects and has a better effect on soil improvement.
[0034] (2) The present invention selects suitable initiators, crosslinking agents and emulsifiers, and controls their dosage and the mass ratio of β-cyclodextrin, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide to obtain a β-cyclodextrin-2-acrylamido-2-methylpropanesulfonic acid-acrylamide copolymer with moderate molecular weight and ionicity. The copolymer is applied to improve saline-alkali land, which can effectively improve soil physical properties, increase the number of water-stable aggregates in soil, reduce soil bulk density, increase permeability and porosity, increase soil moisture content, and maintain a good soil structure. DETAILED DESCRIPTION
[0035] The features described above in the present invention, or in the embodiments, may be combined in any combination. All features described in this specification may be used in conjunction with any method or form, and each feature disclosed in this specification may be replaced by any alternative feature that serves the same, equivalent, or similar purpose. Therefore, unless otherwise specified, the features disclosed are merely general examples of equivalent or similar features.
[0036] The present invention will be further described below in conjunction with specific examples. These examples are intended to illustrate the present invention only and are not intended to limit the scope of the invention. The following examples are implementation methods for which specific conditions are noted, generally according to conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise specified, all percentages and fractions are by weight.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those known to those skilled in the art. Furthermore, any methods and materials similar or equivalent to those described herein can be applied to the methods of the present invention. The preferred methods and materials described herein are for illustrative purposes only.
[0038] Example 1 The preparation method of β-cyclodextrin-2-acrylamide-2-methylpropanesulfonic acid-acrylamide copolymer comprises the following steps:
[0039] (1) adding 0.2 g / mL sodium hydroxide solution to β-cyclodextrin until it is completely dissolved to obtain a β-cyclodextrin alkaline solution;
[0040] (2) adding the cyclohexane solution to the β-cyclodextrin alkaline solution (volume ratio 4:1), stirring rapidly until dispersed, and then adding 0.2% of the total weight of the monomers, 0.03% of N,N-2-methylbisacrylamide, and 5% of Tween-80, stirring until a stable emulsion is formed;
[0041] (3) adding acrylamide to water (mass-to-volume ratio of 0.15 g / mL), stirring until completely dissolved, and then adding 2-acrylamido-2-methylpropanesulfonic acid to obtain a mixed solution;
[0042] (4) heating the emulsion obtained in step (2) under reflux under nitrogen protection, and when the temperature rises to 40° C., adding the mixed solution of step (3) dropwise to the emulsion at a rate of 1-2 drops per second, and gradually heating to 60° C. at a rate of 1° C. per 2-3 minutes. After the reaction is completed, demulsification is performed with anhydrous ethanol, and the mixture is repeatedly washed with anhydrous ethanol, and dried at 40° C. for 30 hours to obtain the β-cyclodextrin-2-acrylamido-2-methylpropanesulfonic acid-acrylamide copolymer;
[0043] The mass ratio of the β-cyclodextrin, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide is 0.5:1:5. Example 2 The preparation method of the β-cyclodextrin-2-acrylamido-2-methylpropanesulfonic acid-acrylamide copolymer comprises the following steps:
[0044] (1) adding 0.35 g / mL sodium hydroxide solution to β-cyclodextrin until it is completely dissolved to obtain a β-cyclodextrin alkaline solution;
[0045] (2) adding the cyclohexane solution to the β-cyclodextrin alkaline solution (volume ratio 6:1), stirring rapidly until dispersed, and then adding 0.4% of the total weight of the monomers, 0.06% of N,N-2-methylbisacrylamide, and 8% of Tween-80, stirring until a stable emulsion is formed;
[0046] (3) adding acrylamide to water (mass-to-volume ratio of 0.20 g / mL), stirring until completely dissolved, and then adding 2-acrylamido-2-methylpropanesulfonic acid to obtain a mixed solution;
[0047] (4) heating the emulsion obtained in step (2) under reflux under nitrogen protection, and when the temperature rises to 40° C., adding the mixed solution of step (3) dropwise to the emulsion at a rate of 1-2 drops per second, and gradually heating the emulsion to 60° C. at a rate of 1° C. per 2-3 minutes. After the reaction is completed, demulsification is performed with anhydrous ethanol, and the emulsion is repeatedly washed with anhydrous ethanol, and dried at 50° C. for 20 hours to obtain the β-cyclodextrin-2-acrylamido-2-methylpropanesulfonic acid-acrylamide copolymer;
[0048] The mass ratio of the β-cyclodextrin, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide is 2:1.5:7. Example 3 The preparation method of the β-cyclodextrin-2-acrylamido-2-methylpropanesulfonic acid-acrylamide copolymer comprises the following steps:
[0049] (1) adding 0.25 g / mL sodium hydroxide solution to β-cyclodextrin until it is completely dissolved to obtain a β-cyclodextrin alkaline solution;
[0050] (2) adding the cyclohexane solution to the β-cyclodextrin alkaline solution (volume ratio 5.5:1), stirring rapidly until dispersed, and then adding 0.3% of the total weight of the monomers, 0.04% of N,N-2-methylbisacrylamide, and 6% of Tween-80, stirring until a stable emulsion is formed;
[0051] (3) adding acrylamide to water (mass-to-volume ratio of 0.16 g / mL) and stirring until completely dissolved, and then adding 2-acrylamido-2-methylpropanesulfonic acid to obtain a mixed solution;
[0052] (4) heating the emulsion obtained in step (2) under reflux under nitrogen protection, and when the temperature rises to 40° C., adding the mixed solution of step (3) dropwise to the emulsion at a rate of 1-2 drops per second, and gradually heating to 60° C. at a rate of 1° C. per 2-3 minutes. After the reaction is completed, demulsification is performed with anhydrous ethanol, and the mixture is repeatedly washed with anhydrous ethanol, and dried at 40° C. for 25 hours to obtain the β-cyclodextrin-2-acrylamido-2-methylpropanesulfonic acid-acrylamide copolymer;
[0053] The mass ratio of the beta-cyclodextrin, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide is 0.8:1.2:6.5.
[0054] Comparative Example 1
[0055] The difference from Example 3 is that 2-acrylamido-2-methylpropanesulfonic acid is replaced by acrylic acid, and the rest is the same as Example 3.
[0056] Comparative Example 2
[0057] The difference from Example 3 is that 2-acrylamido-2-methylpropanesulfonic acid is replaced by sodium p-styrenesulfonate, and the rest is the same as Example 3.
[0058] Comparative Example 3
[0059] The difference from Example 3 is that Tween 80 is replaced by Span 80, and the rest is the same as Example 3.
[0060] Performance data
[0061] 1. Determination of characteristic viscosity, anionicity and acrylamide residue
[0062] The characteristic viscosity was determined by the one-point method;
[0063] The anionicity was determined by hydrochloric acid titration;
[0064] The residual acrylamide content was determined by the bromine addition method.
[0065] The test results are shown in Table 1 below.
[0066] Table 1
[0067] Characteristic viscosity (mL / g) Anionicity (%) Acrylamide residue (%) Example 1 1098 28.4 0.21 Example 2 1125 27.2 0.20 Example 3 1158 29.5 0.18 Comparative Example 1 984 18.1 0.28 Comparative Example 2 1012 19.5 0.24 Comparative Example 3 968 20.8 0.25
[0068] The test results in Table 1 above indicate that the anionic polyacrylamide prepared using the method provided by the present invention has a high characteristic viscosity and a moderate anionicity, and the reaction is relatively thorough, resulting in low residual acrylamide. Anionicity is a key factor influencing the formation of cationic bridges. A certain anionicity is a prerequisite for PAM to be absorbed by soil particles. The anionic polyacrylamide prepared by the present invention has an anionicity between 25% and 30%, which can better disperse the bridging action between soil fine particles and form a protective net on the outer surface of the aggregates, thereby achieving excellent results in soil and water conservation.
[0069] 2. Water absorption test
[0070] Test method: Weigh the prepared anionic polyacrylamide sample, add it to distilled water, allow it to adsorb at room temperature for 3 hours, filter it with a sieve, weigh it, and calculate its water absorption rate Q according to the formula:
[0071] Q=(m2-m1) / m1
[0072] Where Q is the water absorption rate (g / g); m1 is the mass of the sample (g); m2 is the mass of the resin after absorption (g).
[0073] The test results are shown in Table 2 below.
[0074] Table 2
[0075] Water absorption rate g / g Example 1 612 Example 2 624 Example 3 628 Comparative Example 1 592 Comparative Example 2 589 Comparative Example 3 564
[0076] According to the test results in Table 2 above, it can be seen that the anionic polyacrylamide prepared by the method provided by the present invention has high water absorption, and the water absorption rate in 3 hours can reach more than 600 g / g. In the comparative example, changing the type of anionic monomer or changing the type of emulsifier will affect the water absorption effect of the product.
[0077] It will be understood that the above embodiments are merely exemplary embodiments for the purpose of illustrating the present invention, and the present invention is not limited thereto. Those skilled in the art will appreciate that various modifications and improvements can be made without departing from the spirit and substance of the present invention, and such modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. An anionic amide polymer, characterized in that: The anionic amide polymer is a β-cyclodextrin-2-acrylamide-2-methylpropanesulfonic acid-acrylamide copolymer, which is prepared by the following method: (1) adding sodium hydroxide solution to β-cyclodextrin until it is completely dissolved to obtain a β-cyclodextrin alkaline solution; (2) adding the cyclohexane solution to the β-cyclodextrin alkaline solution, stirring rapidly until dispersed, then adding an initiator, a crosslinking agent and an emulsifier, and stirring until a stable emulsion is formed; (3) adding acrylamide to water, stirring until completely dissolved, and then adding 2-acrylamido-2-methylpropanesulfonic acid to obtain a mixed solution; (4) The emulsion obtained in step (2) is heated to reflux under nitrogen protection. When the temperature rises to 40° C., the mixed solution of step (3) is added dropwise to the emulsion, and the temperature is gradually raised to 60° C. After the reaction is completed, anhydrous ethanol is used to break the emulsion, wash, and dry to obtain the β-cyclodextrin-2-acrylamide-2-methylpropanesulfonic acid-acrylamide copolymer.
2. The anionic amide polymer according to claim 1, characterized in that: The concentration of sodium hydroxide described in step (1) is 0.2-0.35 g / mL.
3. The anionic amide polymer according to claim 1, characterized in that: The initiator described in step (2) is coupled diisobutyronitrile; the cross-linking agent is N,N-2-methylbisacrylamide; and the emulsifier is Tween-80.
4. The anionic amide polymer according to claim 1, characterized in that: The volume ratio of the cyclohexane solution to the β-cyclodextrin alkaline solution in step (2) is 4-6:
1.
5. The anionic amide polymer according to claim 1, characterized in that: The mass ratio of the beta-cyclodextrin, 2-acrylamide-2-methylpropanesulfonic acid and acrylamide is 0.5-2:1-1.5:5-7.
6. The anionic amide polymer according to claim 5, characterized in that: The mass ratio of the beta-cyclodextrin, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide is 0.8:1.2:6.
5.
7. The anionic amide polymer according to claim 1, characterized in that: The added amount of the initiator is 0.2-0.4% of the total mass of the monomers; the added amount of the crosslinking agent is 0.03-0.06% of the total mass of the monomers; and the added amount of the emulsifier is 5-8% of the total mass of the monomers.
8. The anionic amide polymer according to claim 1, characterized in that: The dripping speed in step (4) is 1-2 drops per second; the heating speed is 1°C in 2-3 minutes.
9. The anionic amide polymer according to claim 1, characterized in that: The washing solvent in step (4) is anhydrous ethanol; the drying temperature is 40-50° C., and the drying time is 20-30 hours.
10. Use of the anionic amide polymer according to any one of claims 1 to 9 in the preparation of a soil conditioner.
Citation Information
Patent Citations
Method for improving soil structure of coastal dredge fill
CN102487618A
Soil improvement method
CN106922245A
New process for the preparation of inverse latex of acrylamide-based polymers and composition comprising said latex
CN101835817A
Acrylamide / 2-acrylamido-2-methylpropane sulfonic acid sodium / cyclodextrin modified acrylamide (AM / AMPS-Na / MAM) copolymer and preparation method thereof
CN102199251A
Preparation method of hydrophobically associating polymer inverse emulsion
CN105418840A